Pengaruh Gaya Kepemimpinan dan Kedisiplinan Pegawai Terhadap Peningkatan Efektifitas Kerja - Habsy, M Hafiz Al; Purnomo, Dwi; Suri, Rinjani Devina; Jefia, Ratih; Syafrinaldi, Syafrinaldi; Syamsir, Syamsir (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
Leadership style as a way of directing and managing all elements within an organization has a significant influence on the achievement of an organization. Leadership style requires appropriate placement according to needs, so leadership style will determine the quality of an organization's work in achieving its goals. This study aims to describe the style and influence of leadership and discipline on employee work effectiveness at PT. Mamypoko's Padang branch. The research was conducted using qualitative methods and a descriptive approach. Specifically, this study found that the leadership style applied at PT. Mamypoko's Padang branch is a mix of several leadership styles, namely democratic and bureaucratic. This can be seen from the monitoring attitude shown by leaders in managing and directing all elements within the organization. The substantive conclusion of this article is that the use of several leadership style models in a workplace will improve the quality of work of employees.